Analysis of Relationship Marketing Lifestyle Consumer Attitudes on Purchasing Decisions and their impact on Loyalty for MSME Products Made from Sea Products in Sidoarjo Regency. - Setyowati, Dyah Eko; Hambalah, Febrina (International Journal of Artificial Intelligence Research, 2024)
Lifestyle and consumer behavior are influenced by the rapid development of technology, the digital world and the internet of course also have an impact world of marketing. Marketing trends are shifting from conventional (offline) to digital (online). This digital marketing strategy is more prospective because it allows potential customers to obtain information about products and make transactions via the internet. Various digital marketing activities include search engine optimization (SEO), search engine marketing (SEM), content marketing, influencer marketing, content automation, campaign marketing, E-Commerce marketing, social media marketing, social media optimization, e-mail direct marketing, display advertising, e-books, optical disks, games, and various other forms of digital media. Its activities can also be extended to non-internet channels that provide digital media services, such as mobile phones (SMS and MMS).Several indicators that can be used currently include the increase in digital advertising expenditure, growth in smartphone ownership which provides easy internet access, improvements to telecommunications infrastructure in order to increase the quality of data access, and the launch of 4G services. According to Facebook data, 74% of internet users in Indonesia use mobile devices (Utomo, 2016) Quoting the report, We are Social (2023)a digital marketing agency in America, saidFacebook is the platform with the highest number of active users, reaching 2.9 billion as of January 2023. Followed by the YouTube platform with the number of active users reaching 2.2 billion. This research is quantitative research, which according to Creswell is quantitative research as an effort to investigate problems. Where this problem is the basis for researchers to collect data, determine variables and then measure them with numbers so that analysis can be carried out in accordance with applicable statistical procedures. The selection of research locations was carried out using a purposive sampling method, namely a technique for selecting research locations deliberately by considering certain aspects. In this research, hypothesis testing uses the Partial Least Square (PLS) analysis technique with the Smart PLS programThe inner model or what is usually called an influence test or hypothesis test aims to predict relationships between latent variables.From the research conclusions, it can be suggested to marine product business players, to maintain profits and consistently increase sales, good management of relationships, lifestyle and consumer attitudes must be carried out. By maintaining relationships with the media, promotional tools, digital marketing. Consumer lifestyles must also be maintained by holding events that focus on seafood-based foods, including by synergizing with holding Food Festivals, seafood cooking courses, introducing seafood so that Gen Z will be more popular. For consumer attitudes, this can be done with massive publicity, intensive, about the importance of seafood and its benefits, the importance of seafood for body health and stamina.